Demonstration of Helical Antenna Stability Beyond C-Band Frequency - Rahul Yadav (International Journal of Informatics and Communication Technology (IJ-ICT), 2013)
The paper demonstrates design of helical antenna to achieve stable frequency response and impedance matching beyond C-band microwave frequency. An impedance matching cavity is developed for excitation of higher order modes along with the fundamental mode in the helical antenna. Triple frequency bands are resonated by loading the designed helical antenna inside the cavity and a dual band response is realized by introducing variation in feed pin height with an incremental offset of 0.1λ to the initial height which is taken as 0.2λ. The broadband gain for all the designs and a detail analysis of modes along the helical antenna loaded in rectangular cavity is reported. A highest measured bandwidth of 5.4 GHz and a peak gain of 10.65 dB is obtained. The antenna being compact and conformal in design may find its application for terrestrial, aerospace communication and personal wireless communication.DOI: http://dx.doi.org/10.11591/ij-ict.v2i3.4861